DJ-1 is a reliable serum biomarker for discriminating high-risk endometrial cancer - Annalisa Di Cello; Maddalena Di Sanzo; Francesca Marta Perrone; Gianluca Santamaria; Erika Rania; Elvira Angotti; Roberta Venturella; Serafina Mancuso; Fulvio Zullo; Giovanni Cuda; Francesco Costanzo (Tumor Biology)
New reliable approaches to stratify patients with endometrial cancer into risk categories are highly needed. We have recently demonstrated that DJ-1 is overexpressed in endometrial cancer, showing significantly higher levels both in serum and tissue of patients with high-risk endometrial cancer compared with low-risk endometrial cancer. In this experimental study, we further extended our observation, evaluating the role of DJ-1 as an accurate serum biomarker for high-risk endometrial cancer. A total of 101 endometrial cancer patients and 44 healthy subjects were prospectively recruited. DJ-1 serum levels were evaluated comparing cases and controls and, among endometrial cancer patients, between high- and low-risk patients. The results demonstrate that DJ-1 levels are significantly higher in cases versus controls and in high- versus low-risk patients. The receiver operating characteristic curve analysis shows that DJ-1 has a very good diagnostic accuracy in discriminating endometrial cancer patients versus controls and an excellent accuracy in distinguishing, among endometrial cancer patients, low- from high-risk cases. DJ-1 sensitivity and specificity are the highest when high- and low-risk patients are compared, reaching the value of 95% and 99%, respectively. Moreover, DJ-1 serum levels seem to be correlated with worsening of the endometrial cancer grade and histotype, making it a reliable tool in the preoperative decision-making process.